Desain Integrasi Sistem Instrumentasi dan Kendali untuk Commissioning Siklotron DECY-13 - Frida Iswinning Diah; Fajar Sidik Permana; Emy Mulyani (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
A cyclotron is a particle beam accelerator used for various applications, one of which is to produce medical radioisotopes. Research Center for Accelerator Technology, Research Organization for Nuclear Energy - National Research and Innovation Agency (Pusat Riset Teknologi Akselerator, Organisasi Riset Tenaga Nuklir - Badan Riset dan Inovasi Nasional, PRTA ORTN-BRIN) is conducting research and development (R&D) for the DECY-13 cyclotron that has reached the stage of testing its primary components. The primary components of the DECY-13 cyclotron consist of seven systems. In commissioning, it is necessary to prepare an integrated instrumentation and control system (ICS) design that unites the operation of all DECY-13 cyclotron’s primary components to produce a particle beam as desired. The integration process was carried out in two stages: determining operating procedures during commissioning and identifying operating parameters; and designing the ICS integration. The process of identifying parameters and determining operating procedures was carried out by studying test data and operating standards for each component to obtain important parameters in operation. Next, the ICS architecture was developed by integrating the operating system on the primary components using the distributed control system (DCS) method. The DCS configuration consisted of three layers, namely the operator, the main control, and the device layers. Communication between the device and the main control layers was carried out using the RS-232 serial communication, while the communication between the main control and the operator layers used the Ethernet. The RS-232 communication between the device and main control layers was used to manage data acquisition, data logging, and operation control. At the operator layer, there was a host-PC that functioned as a data viewer and data logging. This design is expected to be a guide in the implementation of ICS improvements, and realizing ease during commissioning.